Radially oriented functional thermal materials prepared by flow field-driven self-assembly strategy. (15th December 2022) - Zhang, Xinfeng; Xie, Bin; Zhou, Shuling; Yang, Xuan; Fan, Yiwen; Hu, Run; Luo, Xiaobing
Abstract: Filler-reinforced polymer composites are widely applied in thermal management field on account of their promising heat transport ability, superior flexibility and excellent durability. Inside these composites, thermally conductive fillers are usually uniformly distributed or unidirectionally oriented in polymer matrix to improve thermal performances. However, the ever-shrinking and spatially distributed heat sources in three-dimensional, high-density packaged electronic devices have created the localized "hotspot" problem, which raises a new challenge and stricter requirement for the composite thermal materials. Inspired by the amazing radial microstructures in ginkgo leaf, we proposed a flow field-driven self-assembly strategy to fabricate functional thermal materials with radially oriented carbon fibers (CFs). To quantitively evaluate the orientation, an orientation algorithm based on microscale image identification was developed, and an evaluation criterion was proposed. The underlying orientation mechanisms of fillers under the driving of flow field were revealed by visual simulation of vacuum filtration. Thanks to the well-oriented fillers architecture, the composites demonstrated an ultrahigh in-plane thermal conductivity of 35.5 W/(m∙K) with a thermal conductivity anisotropy of 19.8, which enables rapid and efficient heat dissipation pathways towards localized hotspots. In addition, this flow field-driven self-assembly strategy provides a promising self-design ability that is expected to solve the heat dissipation of arbitrary-shape heat sources, and shed light on other application scenarios like efficient solar-thermal-electric conversion. Graphical Abstract: ga1 Highlights: Thermally conductive composites with radial structure were prepared by a flow field-driven self-assembly strategy. To quantitively evaluate the orientation, an orientation algorithm and an evaluation criterion were proposed. The underlying orientation mechanisms of fillers under the driving of flow field were revealed by visual simulation. Ra/0.80/7-composite showed an in-plane thermal conductivity of 35.5 W/(m∙K) with a thermal conductivity anisotropy of 19.8.